MEDIA SOSIAL INSTAGRAM DAN CONTENT MARKETING KEPUTUSAN PEMBELIAN KONSUMEN TOSERBA YOGYA SUKABUMI - Rianto, Toha; Setiadi, Sandi; Laila, Delian (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to determine the influence of Instagram social media and content marketing on consumer purchasing decisions at Toserba Yogya Sukabumi. In facing the digital era and the rapid growth of e-commerce, Toserba Yogya Sukabumi strives to increase competitiveness through social media as a means of promotion and interactive communication. However, the stagnation of the number of followers and low content interaction are challenges. This study uses a quantitative method with an associative approach and involves 99 respondents who are followers of the Toserba Yogya Sukabumi Instagram account. The results show that Instagram social media has a positive and significant partial effect on purchasing decisions with a calculated t value of 5.294 > t table 1.985 and a significance of 0.000 < 0.05. Content marketing also has a positive and significant effect with a calculated t value of 4.174 > t table 1.985 and a significance of 0.000 < 0.05. Simultaneously, both variables significantly influenced purchasing decisions, with an F-value of 367.920 > F-table of 2.70 and a significance level of 0.000 < 0.05. The adjusted R2 value of 0.882 indicates that 88.2% of the variation in purchasing decisions was influenced by these two variables. This finding underscores the importance of interactivity and content quality in digital marketing strategies to improve retail consumer purchasing decisions.